Perencanaan Distribusi LPG dengan Periodic Vehicle Routing Problem guna Minimasi Biaya Transportasi (Studi Kasus : PT.Gading Mas Indah Malang) - Annisa Kesy Garside; Nyimas Mirnayanti Jayasari Sutadisastra (Performa: Media Ilmiah Teknik Industri, 2010)
PT. Gading Mas Indah Malang represent one of LPG distributor which has a handling of inefficient distribution problem in delivery process to agent where less gives attention to demand, no definite scheduling and route make the high of distribution cost. Periodic Vehicle Routing Problem (PVRP) is a route planning from a depot to consumer among m-day period. In this research, PVRP used to optimize visit frequency and route of each agent to minimize distribution cost. The first step is clustering agents by k-means approach then determining delivery quantity, formulate mathematical model of PVRP, and solution searching using LINGO software to select the route which gives the minimum cost. From the result, optimum visit frequency is 1 visit and transportation cost saving is Rp 733,500,-/week equal to 40.82%.